PENERAPAN APLIKASI MOBILE JKN DALAM UPAYA MENINGKATKAN AKSES PELAYANAN KESEHATAN MASYARAKAT DESA WIBAWAMULYA - Hafidz, Shohibul; Siaga Pangestuti, Rinda; Qintharah, Yuha Nadhirah (Universitas Islam 45 Bekasi, 2024)
The application of information and communication technology is important in various sectors, including the health sector. The application of information and communication technology in the National Health Insurance (JKN) application in Indonesia has been used by BPJS Kesehatan. JKN aims to protect all Indonesian citizens with a compulsory health insurance system. The method of implementing community service is community education through JKN socialisation using presentations, discussions, and questions and answers. The results of community service on the socialisation of JKN mobile applications in an effort to facilitate access to health services for the Wibawamulya Village community provide benefits or impacts, namely knowledge about the functions and benefits of the JKN Mobile application, so that the community can get maximum health services. With this event, the village head pays more attention to his community to get health care facilities in Wibawamulya Village.